Covid-19 Dan Pengaruhnya Terhadap Perilaku Hidup Bersih Masyarakat Muslim - Amrullah, Amrullah; Jubba, Hasse; Maysharah, Siti (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
Coronavirus disease also known as Covid-19 forces society to adapt and change to encounter and stop its spread. Maintaining personal and environmental cleanliness is the method suggested by WHO and the government for dealing with the pandemic. Islam has taught about the virtue of cleanliness in the Quran and hadith long before the Covid-19 pandemic. Likewise, religious authorities such as the MUI issued a fatwa on the topic long before the coronavirus arrived in Indonesia. This research used the literature review method to understand Muslim society's awareness of cleanliness and the impact of Covid-19 on its behaviors. It discovered that the ideal expected of Islam to be aware of cleanliness still showed a gap over the reality that occurred, particularly in Indonesia, which has the world's largest Muslim population. However, the arrival of the Covid-19 pandemic in Indonesia has had a positive impact on personal cleanliness. According to a BPS survey, the majority of respondents are more likely to adopt hygiene behavior. Furthermore, Islamic organizations such as MUI, Muhammadiyah, and NU have long emphasized the importance of maintaining personal and environmental cleanliness. One of the lessons of the Covid-19 pandemic is the importance of cleanliness, particularly in daily life.